ANALISIS INDEKS KINERJA DAERAH IRIGASI KOYA KOTA JAYAPURA - Raymond Maurits; Mujiati Mujiati; Bahtiar Bahtiar (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
Jayapura City chose Muara Tami District as the center for agribusiness and agro-tourism, which then made the Kelurahan Koya Barat and Koya Timur as food barns. The Koya area started from the transmigration area program at that time people who came from the Javanese and Sulawesi ethnic groups. After developing, now it has been able to meet the food needs of Jayapura City and Jayapura Regency. The purpose of this study was to evaluate the performance of the irrigation network for the Koya Irrigation Area in the hope of increasing agricultural production and reducing Operation and Maintenance (OP) costs according to a priority scale. The method used is direct observation in the field by tracing the irrigation network of D.I Koya and interviews with farmers and officers. The results obtained and the results of data analysis are the performance of the main irrigation network system in Koya which includes aspects of physical infrastructure, supporting facilities, plant productivity, personnel organization, documentation and associations of water user farmers (P3A) which is 68.40% in the category of poor performance and needs attention. , the handling is routine maintenance, periodic maintenance and rehabilitation